Efficacy and safety of dapsone in adult primary immune thrombocytopenia - Marion Larue; Guillaume Moulis; Manuela Rueter; Sylvain Audia; Thibault Comont; Louis Terriou; Jean-François Viallard; Brigitte Pan-Petesch; Bruno Royer; Bernard Bonnotte; Lionel Galicier; Olivier Lambotte; et al. (Blood Advances)
Abstract: To assess efficacy and safety of dapsone in adult immune thrombocytopenia (ITP), a multicenter randomized controlled trial (RCT) and a real-world cohort study were performed. Participants were adults with primary ITP, transient response to corticosteroids with/without intravenous immunoglobulin, and a platelet count of ≤30 × 109/L (or ≤50 × 109/L with bleeding). Patients in the RCT were randomized in arm A (prednisone × 3 weeks + dapsone for 12 months) or arm B (prednisone alone). The observational study involved dapsone initiation at 100 mg/d with standard follow-up. The primary end point was the response rate (platelet count of >30 × 109/L and ≥2× baseline level) at 52 weeks, with the response rate at 24 weeks and adverse events as secondary end points. The RCT enrolled 93 patients (54.8% female), with median age of 48.5 years (46 years in arm A; and 47 years in arm B). In the intention-to-treat analysis, 78.3% of patients in arm A discontinued dapsone after a median of 4.6 weeks because of adverse events (66.7%) or lack of efficacy (33.3%). The response rate at week 52 was 21.7% (95% confidence interval [CI], 10.9-36.4) in arm A vs 8.5% (95% CI, 2.7-18.6) in arm B (P = .17). The observational study, which was conducted after the end of the RCT, included 46 patients (52.2% female), median age of 50.7 years. Adverse events occurred in 30.4%, leading to discontinuation of dapsone in 23.9%, and 13.6% (95% CI 5.2-27.4) met the primary efficacy end point. Results from both studies showed an unfavorable risk-benefit ratio for the use of dapsone in adult primary ITP and suggest that, whenever available, second-line options should be used. This trial was registered at www.ClinicalTrials.gov as #NCT02627417 and #NCT02877706.